Комбінована ксенотрансплантація як метод пролонгації життєздатності та функціонування трансплантата під час лікування різних форм гіпокортицизму - Ларін, О. С.; Анастасій, Л. В.; Гирявенко, О. Я.; Січінава, Р. М. (Clinical Endocrinology and Endocrine Surgery, 2013)
The revue is dedicated to the possibility of application combined xenotransplantation of adrenal gland organ cell culture with hepatocytes in complex therapy of various forms hypocorticism, and also as a way to prevent the formation of the pituitary gland adenoma. Taking into account the substantial part of the bibliographical sources we arrived at the output, that joint cultivation of tissues of adrenal glands and liver newborn piglets promotes to the increase of adrenocorticocytes functional activity and after their joint xenotransplantation to patients with different forms of hypocorticism prolonged the period of disease compensation and decreasing corticosteroid doses, used as replacement therapy.